Selection of Candidates for Lung Transplantation and Controversial Issues - Orens, Jonathan B.; Merlo, Christian A. (Seminars in Respiratory and Critical Care Medicine, 2018)
Lung transplantation is a widely accepted treatment to manage the advanced stages of many lung diseases that have failed to respond to all other therapeutic interventions. There have been ever-expanding indications for lung transplantation as a treatment for lung disease. The International Society for Heart and Lung Transplantation (ISHLT) updated guidelines for candidate selection in 2014. This document was published to serve as a guide in selecting appropriate candidates for lung transplantation. Ideal candidates for lung transplantation are those with near-end stage disease, limited life expectancy due to their lung disease, and who experience significant loss in quality of life. At the same time, candidates should be free of significant comorbidities that might negatively impact successful transplantation. Despite well thought out published guidelines for candidate selection, many controversial issues surrounding selection of lung transplant candidates remain. This review will focus on some of the more common controversial issues and explain how most centers approach these issues when choosing candidates for lung transplantation.
Keywords: lung transplantation; indications; candidate selection